A novel pathway for the production of H2S by DAO in rat jejunum. Issue 5 (27th January 2016) - Tang, S.; Huang, D.; An, N.; Chen, D.; Zhao, D.
Abstract: Background: Hydrogen sulfide (H2 S) is endogenously generated from L‐cysteine (L‐Cys) by the enzymes cystathionine‐ β ‐synthase (CBS) and cystathionine‐ γ ‐Lyase (CSE). Hydrogen sulfide is also produced from D‐cysteine (D‐Cys) by D‐Amino acid oxidase (DAO). Methods: The H2 S production was measured by the methylene blue assay. The expression of DAO was investigated by Western blotting and immunohistochemistry. The short‐circuit current ( I sc) was recorded using the Ussing chamber technique. Key Results: The epithelium in rat jejunum possesses DAO, and generates H2 S. D‐cysteine, originally used as a negative control for L‐Cys, significantly increases the H2 S release, which is inhibited by I2CA, an inhibitor of DAO. In vitro study by Ussing chamber technique reveals that D‐Cys decreases the I sc across the epithelium of the rat jejunum and enhances the Na + ‐coupled L‐alanine transport. Conclusions & Inferences: A novel pathway for the production of H2 S by DAO exists in rat jejunum. Abstract : Hydrogen sulfide is produced from D‐cysteine (D‐Cys) in rat jejunum. D‐Amino acid oxidase (DAO) exists in rat jejunum. D‐cysteine evokes a short‐circuit current across epithelium of rat jejunum. D‐cysteine enhances the Na+‐coupled L‐alanine transport.